2017
DOI: 10.21873/anticanres.11680
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use Does Not Appear to Influence Response to Nivolumab

Abstract: Microbiota modification induced by antibiotics does not appear to affect the efficacy of nivolumab in patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 19 publications
1
51
1
Order By: Relevance
“…26 In addition, Kaderbhai et al found that ATB use 3 months before nivolumab immunotherapy did not affect the clinical efficacy of ICI. 29 It should be noted that the favorable results of ATB use 60 days prior to therapy could also be due to recall bias over the unavailability of ATB treatment data in retrospective studies. Thus, future large-scale, prospective studies are required to investigate the impact of the use time, duration, route, and drug type of ATBs on the clinical efficacy of ICI immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 In addition, Kaderbhai et al found that ATB use 3 months before nivolumab immunotherapy did not affect the clinical efficacy of ICI. 29 It should be noted that the favorable results of ATB use 60 days prior to therapy could also be due to recall bias over the unavailability of ATB treatment data in retrospective studies. Thus, future large-scale, prospective studies are required to investigate the impact of the use time, duration, route, and drug type of ATBs on the clinical efficacy of ICI immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 19 studies were included in our quantitative analysis ( Figure 1). 10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] A total of 2,740 patients [mean: 144; median with range: 109 (30-360)] were included in our analysis. The included studies were published between 2017 and 2019 (17/19 studies, 89%, were published in 2018 and 2019) from the United States, the United Kingdom, China, Japan, Canada, Switzerland, Greece, Korea, Austria, and France.…”
Section: Study Selection and Associated Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This, in turn, induces the expression of immune checkpoint molecules, including PD-L1 on various cells. Therefore, in patients after acute infection and antibiotic therapy, the effect of immunotherapy may be negligible [12].…”
Section: Review Of the Literaturementioning
confidence: 99%